Food allergens : analysis instrumentation and methods - Nollet, Leo M. L., 1948-; Hengel, Arjon J. van (Boca Raton : Taylor & Francis, 2011)
'Covering all of the major recognized food allergens in the US and EU, this comprehensive work begins with an introduction to the problem and prevalence of food allergens. It discusses health issues and the presence of allergens in various food products, examines methodologies for analysis and detection, and details specific methods for each food type. Maintaining a consistent structure and format throughout, each chapter describes the properties of the allergen, and demonstrates the appropriate sample extraction and clean-up, separation and analysis, and detection and quantification techniques'--Provided by publisher
(Publisher-supplied data) Methodology, Phil E. Johnson, Ana I. Sancho,Rene W.R. Crevel, and E.N. Clare Mills -- Allergens in peanut, soybean and lupin, Christiane Fste -- Allergens in tree nuts, sesame seeds, mustard and celery, Thomas Holzhause and Martin Roder -- Allergens in milk and egg, Angelika Paschke -- Allergens in cereals, Dimosthenis Kizis and George Siragakis -- Fish, crustaceans and mollusks, Poi-Wah Lee and Steve L. Taylor
Includes bibliographical references and index
Keywords: Allergens -- Immunology; Food Hypersensitivity -- immunology; Allergens -- Analysis